Adaptive Second-Order Fast Terminal Sliding-Mode Formation Control for Unmanned Surface Vehicles - Wang, Duansong; Kong, Min; Zhang, Gang; Liang, Xiaoling (Journal of marine science and engineering, 2022)
The formation control of unmanned surface vehicles (USVs) while considering communication topology, dynamic model uncertainties, environmental disturbances, and a fast convergence rate is addressed in this paper. First, graph theory is introduced to describe the connective relationships and establish generalized formation errors among USVs. Then, a second-order fast nonsingular terminal sliding-mode control (SOFNTSMC) is designed to guarantee that the system converges quickly and without chatter. An adaptive update law is designed in order to estimate the model uncertainties and external disturbances without the requirement of the boundary information of the system uncertainties. With the application of the adaptive SOFNTSMC (ASOFNTSMC) and graph theory, a distributed control is developed for every USV to perform the desired formation pattern. Finally, the results of simulations and comparisons demonstrate the effectiveness of the proposed method.